Isolated histoplasmosis of the tongue: A case report - Sittiwattanawong, Prattana; Pongprutthipan, Marisa (Chulalongkorn Medical Journal, 2023)
Histoplasmosis is an endemic, systemic mycosis caused by Histoplasma capsulatum. Clinical manifestations are various depending on immunity status. We reported a case of isolated histoplasmosis of the tongue. A 48-year-old Thai woman, steroid-dependence systemic lupus erythematosus, presented with rapid-growing, painful mass on the right lateral aspect of the tongue without systemic symptoms. Histologic examination confirmed the diagnosis of histoplasmosis and tissue culture identified Histoplasma capsulatum. The patient received oral itraconazole for 6 months until the lesion was completely healed. The oral lesions of histoplasmosis could be a part of localized form or disseminated form. We should investigate for possible dissemination or any pulmonary involvement due to different prognosis and treatment plan in the patient with oropharyngeal lesion presentation.